Ádám és a Gólem: A Haszid Szekvenciák teremtésmotívumai a zsidó hagyomány tükrében - Száz, Pál (Studia Litteraria, 2016)
The present study attempts to analyze kabbalistic motifs in the poetic cycle Hasidic Sequences by Szilárd Borbély, which is included in the amplified third book of the second, extended edition of his poetry volume Halotti pompa [The Splendours of Death – 2006]. By using the theory of transtextuality developed by Gérard Genette, focusing on the elaborated motif-structure gathered around the topic of creation of the world, it is clear that hypertexts, used by the author, are derived from the imaginarium of the creation of late lurianic kabbalah. These pretexts or hypotexts, however, originated from the Talmudic or Biblical sources. In this manner of palimpsestuous reading, the texts reveal their unique bricolage structure, which offers a detailed view of Szilárd Borbély’s writing method.